Stress Regulation via Being in Nature and Social Support in Adults, a Meta-Analysis - Sparacio, Alessandro; Ropovik, Ivan; Jiga-Boy, Gabriela; Lagap, Adar Cem; IJzerman, Hans (Univ California Press, 2023)
In this meta-analysis, the authors investigated whether being in nature and emotional social support are reliable strategies to downregulate stress. We retrieved all the relevant articles that investigated a connection between one of these two strategies and stress. For being in nature we found 54 effects reported in 16 papers (total N = 1,697, MdnN = 52.5), while for emotional social support we found 18 effects reported in 13 papers (total N = 3,787, MdnN = 186). Although we initially found an effect for being in nature and emotional social support on stress (Hedges' g =-.42; Hedges' g =-.14, respectively), the effect only held for being in nature after applying our main publication bias correction technique (Hedges' g =-.60). The emotional social support literature also had a high risk of bias. Although the being-in-nature literature was moderately powered (.72) to detect effects of Cohen's d = .50 or larger, the risk of bias was considerable, and the reporting contained numerous statistical reporting errors.
Ropovik, Ivan/0000-0001-5222-1233; Lagap, Adar Cem/0000-0002-4912-0578
Keywords: Stress Regulation; Being In Nature; Social Support; Meta-Analysis; Registered Report